On (m,n) (U,R) – Centralizers - H. Majeed, Abdulrahmam; F.Ghalib, Haneen (Iraqi Journal of Science, 2023)
Let m ≥ 1,n ≥ 1 be fixed integers and let R be a prime ring with char (R) ≠2 and(m+n). Let T be a (m,n)(U,R)-Centralizer where U is a Jordan ideal of R and T(R)⊆ Z(R) where Z(R) is the center of R ,then T is (U,R)- Centralizer.